Utilization of Video-based Laboratory (VBL) Using Tracker for Analysis of Object Motion on the Laboratory-Scaled Mini Roller Coaster - Sulistyaningsih, Dwi; Maulidah, Rifa'atul; Rifatul Mahmudah, Ifa; Sofi Makiyah, Yanti (KnE Social Sciences, 2024)
The use of teaching aids in learning can provide direct learning experiences to students so that learning becomes more meaningful. Students observe physics phenomena that occur and get physics data from these phenomena. The observed physics phenomena often happen very quickly, so it is impossible to record data manually. Therefore, a method is needed to facilitate data recording and analysis. One way to use a video-based laboratory (VBL) is by utilizing a tracker. This method allows for analyzing the objects contained in a video and displays the data in graphs and tables. This study aims to investigate the motion of objects using tracker video analysis on a mini-roller coaster tool. The video analyzed is a video of a solid ball-shaped object with a mass of 8.6 g moving along a roller-coaster trajectory. By tracking an object, physics data will be obtained to analyze acceleration and the law of conservation of mechanical energy. The analysis results match the experimental results and the physics concepts that apply to the roller coaster motion. Keywords: video-based laboratory (VBL), tracker, laboratory-scaled mini roller coaster